A SINGLE ARM, OPEN LABEL, INTERVENTIONAL STUDY TO EVALUATE THE SAFETY, EFFICACY AND TOLERABILITY OF NEW AMRUTANJAN HEADACHE FASTER RELAXATION ROLL ON FOR PAIN RELIEF IN PATIENTS WITH MIGRAINE HEADACHE DISORDERS - Sakthibalan Murugesan; Ravichandran J; Mohammed Abdul Rasheed A; Gayathri Sivakumar; Selvalaxmi Gnanasegaran; Mahalakshmi Durai (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Migraine is a chronic, recurrent neurological disorder that significantly impacts the quality of life of millions worldwide. Herbal Roll On offers a effective approach to acute migraine pain relief. New Amrutanjan Headache Faster Relaxation Roll On is an ayurvedic proprietary topical preparation formulated with a synergistic blend of Karpura (Camphor), Pudinah (Menthol), and Gandhapura Patra Taila (Oil of Wintergreen)—three well-known natural ingredients with established analgesic and counter-irritant properties. This study was designed as a single-arm, open-label, interventional trial aimed at evaluating the Safety, efficacy and tolerability of New Amrutanjan Headache Faster Relaxation Roll On in participants with migraine headache disorders.Twenty four participants with migraine headache disorders were enrolled in this study and was done for a period of 2 weeks. The enrolled patients received New Amrutanjan Headache Faster Relaxation Roll on twice or thrice daily topically for one day. Participants were monitored throughout the study to evaluate primary and secondary outcome measures.Participants experienced the onset of pain relief rapidly, with an average onset time of 1 minute and 49 seconds after application of the product. Among participants who achieved complete pain relief (n=10), the average time taken was approximately 22 minutes. The mean duration of pain relief following application of the New Amrutanjan Headache Faster Relaxation Roll-On was 111 minutes and 15 seconds. Pain relief was sustained for up to 60–75 minutes before gradually returning. The McGill Pain Questionnaire results confirm that New Amrutanjan Headache Faster Relaxation Roll On effectively reduced multiple dimensions of pain, not just intensity. The participants’ overall satisfaction scores indicated a positive perception of pain relief following product use. 41.7% participants did not require any rescue medication, indicating that the product was effective as a standalone therapy for a substantial proportion of users.In conclusion, the findings from this interventional study support the New Amrutanjan Headache Faster Relaxation Roll On as a safe, well-tolerated, and effective topical option for the relief of migraine headaches. Its rapid onset of action, sustained pain relief, and favorable safety profile make it a promising non-pharmacological adjunct or alternative for migraine management.